Bacillus subtilis HH2 ameliorates TNBS-induced colitis by modulating gut microbiota composition and improving intestinal barrier function in rabbit model. (November 2020) - Luo, Run; Zhang, Jing; Zhang, Xinyue; Zhou, Ziyao; Zhang, Wenping; Zhu, Zeyun; Liu, Haifeng; Wang, Liming; Zhong, Zhijun; Fu, Hualin; Jing, Bo; Peng, Guangneng
Graphical abstract: Abstract: Inflammatory bowel disease (IBD) is known to cause inflammation, as well as intestinal flora and epithelial barrier dysfunction. We evaluated the function of Bacillus subtilis HH2 in a trinitrobenzenesulfonic acid (TNBS)-induced colitis rabbit model through the oral administration of this bacterium. Body weight, disease activity index (DAI) score, and histological changes in the rabbits were recorded. Colons were collected for ELISA, RT-PCR, and western blotting. Intestinal microflora were tested by 16S rRNA sequencing. Results showed that B. subtilis HH2 alleviated body weight loss and decreased the DAI and histological injury scores and also reduced the mRNA expression of TNF-α and IL-1β and enhanced the expression of IL-10. I n addition, B. subtilis HH2 promoted the expression of tight junction proteins, such as occludin, and the expression of related mRNA to maintain the intestinal mucosal barrier function to attenuate colitis symptoms in rabbits. By studying colonic microbiota, we observed that B. subtilis HH2 increased colonic microbial diversity after it was reduced due to TNBS administration; it also increased the relative abundance of the Bifidobacteriaceae family, but the abundances of Bacteroidetes and Proteobacteria were reduced. These results indicated that B. subtilis HH2 could decrease the severity of colitis induced by TNBS by regulating inflammatory cytokines, increasing tight junction proteins, and modulating intestinal microbiota. These findings suggest that the probiotic B. subtilis HH2 might prevent tissue damage due to colitis.